Bedtime vignettes - Agarwal, M. K. (India Partridge, 2014)
The book covers a variety of subjects from everyday life in a literary, provocative and lucid style. The topics extend from 'Seductions of the Bed', 'Travails of a Neighbour', 'The Lure of Junk', 'Celebrating Retirement Day', etc., and on to 'Dangerous Delights'. The treatment is intended to entertain the reader and not to cause him the fatigue of close attention. It is the hope that after he has spent an exhausting day in office or business, the reader will discover in this book some measure of good cheer. But not only at bedtime; he will find in it a good companion whenever he is looking for some leisurely reading - whether on a trip, vacation or weekend holiday. The reader may, as the saying goes, take one sip at a time, that is, go through one piece. But if he be so inclined, he may ingest, with pleasure and profit, more in one sitting.
Keywords: Bedtime story; Leisurely reading